The incorporation of coconut water and banana homogenate in the regeneration of fig (Ficus carica L.) cv. Violette de Solliès - Xin, Jie Lui; Dahmendra Sriskanda,; Wan, Ting Ling; Sreeramanan Subramaniam,; Bee, Lynn Chew (Penerbit Universiti Kebangsaan Malaysia, 2022)
The common fig (Ficus carica L.) is from the family of Moraceae and is commonly cultivated for its fruits, which are well-known for their exceptional nutritional and medicinal properties. The addition of organic additives functions to supply carbon sources and other essential vitamins, minerals, and natural growth regulators to support the growth of explants. The present study aims to assess the effects of coconut water and banana homogenate in the regeneration of Ficus carica cv. Violette de Solliès (VDS). In vitro shoot, explants were cultured in full-strength MS medium without sucrose but with 1.0 mg/L BAP and different concentrations of coconut water and banana homogenate. Results indicated that MS media with 200 mL/L coconut water resulted in the highest number of induced shoots (3.03 ± 0.122) and shoot height (1.005 ± 0.022 cm) compared to other treatments with coconut water, whereas MS media supplemented with 200 g/L banana homogenate produced the highest number of induced shoots (3.00 ± 0.144) and the highest shoot height (0.958 ± 0.020 cm) of all the banana homogenate treatments. In conclusion, coconut water and banana homogenate are suitable alternatives for carbon sources and other organic growth factors contributing to the regeneration of Ficus carica cv. VDS.